Self‐Assembly of Complex DNA Tessellations by Using Low‐Symmetry Multi‐arm DNA Tiles. (8th June 2016) - Zhang, Fei; Jiang, Shuoxing; Li, Wei; Hunt, Ashley; Liu, Yan; Yan, Hao
Abstract: Modular DNA tile‐based self‐assembly is a versatile way to engineer basic tessellation patterns on the nanometer scale, but it remains challenging to achieve high levels of structural complexity. We introduce a set of general design principles to create intricate DNA tessellations by employing multi‐arm DNA motifs with low symmetry. We achieved two novel Archimedean tiling patterns, (4.8.8) and (3.6.3.6), and one pattern with higher‐order structures beyond the complexity observed in Archimedean tiling. Our success in assembling complicated DNA tessellations demonstrates the broad design space of DNA structural motifs, enriching the toolbox of DNA tile‐based self‐assembly and expanding the complexity boundaries of DNA tile‐based tessellation.